Novel self-organized resource management mechanism for large-scale Grid over OBS networks - ZUO Bing; LIU Lei; WU Jian; LIN Jin-tong (Tongxin xuebao)
In order to avoid the problems of client/server（C/S）-based resource management scheme in grid over optical burst switching（OBS） networking,an improved self-organized resource management mechanism based on the peer-to-peer（P2P） technology and the previous works was proposed.By utilizing the P2P technology and special descrip-tion of resources,the proposed mechanism could achieve distributed resource information storage and fast resource dis-covery capability.Simulation results show that the proposed mechanism can not only address the issues of poor scalabil-ity and fault-tolerance introduced by traditional C/S-based schemes,but also reduce the time for resource discovery.Therefore,it is more suitable for future large-scale consumer-oriented optical grid applications.